How geoengineering scientists perceive their role in climate security politics – from concern and unease to strategic positioning. Issue 1 (2nd January 2019) - Svensson, Pernille Cuisy; Pasgaard, Maya
ABSTRACT: Net negative emissions are essential for realizing the two-degree maximum warming target agreed by the world leaders in Paris 2015 for mitigating predicted climate change impacts, which are often framed as threats to human security, globally and locally. Geoengineering offers an immediate response to climate change which might instantly offset these "dangerous" impacts by deliberately altering the climate system to cool the planet. This arguably places geoengineering experts at the centre of future climate change and security policies. Based on empirical data from interviews with renowned geoengineering scientists, this article explores how these geoengineering specialists label and delimit their work when seeking to claim scientific expertise and autonomy from security politics, while arguing for the relevance of their research on climate change. The study shows an ambiguity between how the geoengineering specialists see the scientific potential of their research, and their unease towards the security applications of this very research. A clear distinction between "geoengineering" and "geopolitics" is drawn and upheld using different rhetorical styles, but dissolves when personal strategies and security politics emerge. On this background, the article discusses the imaginary boundary between (security) politics and (geoengineering) expertise, and suggests more transparent and reflexive science in society.